Ausencia parental y el estado socioemocional de los adolescentes del Sector El Mirador de la Parroquia 10 de Noviembre, cantón Ventanas, Provincia de Los Ríos - Calderon Rivas, Damaris Sarahi (2024)
"Parental absence" has a significant impact on the lives of adolescents. It can influence their emotional well-being, psychological development, academic performance, and ability to form social relationships. These and other factors associated with parental absence are analyzed in this research. "Social-emotional state" refers to the combination of social and emotional factors that determine an individual's psychological and social well-being. In this study, descriptive research methodology was used as it is a scientific approach used to describe, explain, and understand particular phenomena. This type of methodology is based on the observation and collection of data from events, situations, individuals, or groups to obtain detailed and accurate information on a specific topic of study. A non-experimental design was used. Non-experimental design is a type of research design that is characterized by the absence of deliberate manipulation of independent variables by the researcher. The study is based on interviews with adolescents living in the El Mirador sector. A population of 70 adolescents was used and 43 adolescents were sampled. The results indicate that the quality of the relationship between parents and children during adolescence can vary significantly depending on the degree of communication, support, and involvement of parents in their children's lives. It also reflected that there are areas of improvement for many adolescents in terms of stress management, decision-making, self-confidence, life satisfaction and emotional coping skills. The importance of understanding and addressing the effects of parental absence on the socio-emotional development of adolescents in the El Mirador sector is highlighted. This includes implementing intervention and support strategies aimed at both adolescents and their families to improve their emotional and social well-being.